Proses Shooting Pembuatan Film “Sabda Rindu” Sebagai Asisten Produser Pada Tim Produksi - Fernanda, Kurnia; Edlina, Ria (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
Film is a part of communication that utilizes technology in several tools such as color and sound which are recommended to convey messages through moving images. In the production process, a short film must go through stages, namely pre-production, production and post-production for the film Sabda Rindu. The process results from those obtained at the pre-production stage, at the production stage the director conducts research to look for ideas for the film to be produced with the team to carry out planning both in determining production time, talent casting, contracts, permits, correspondence and logistics. At the production stage, namely the implementation of shooting, the director and the team work together, where working together here is how individuals can do their work optimally, functionally, well and professionally to realize what is planned in the script into an arrangement of words which then create a picture that tells a story. The post-production stage is recording or rearranging all shooting results based on shooting notes and images. And also the code numbers in the production in the form of digits, frames, seconds, minutes and hours that appear on the image and the results of each shoot are recorded. If anything needs to be added or edited again, revisions will be made as desired until the results are satisfactory.